The Development of Web Based Application for Financial Accountability Report of Indonesian Political Parties - Stevie Kaligis; Maksy Sendiang (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
Accounting for non-profit organizations such as political parties is quite complicated, ranging from planning, execution to assessment, requiring an appropriate management information system to operate and manage the organisation. By optimizing the management information system, the different types of accounting transactions are recorded and economic data is produced to assess the organisation. The aim of this research is to create computer-based financial accounting apps that are used by Indonesia Political Parties to generate accountability and transparency-compliant financial reports to achieve good governance. Research and development method is used in this research. Developing accounting information systems for non-profit organizations is a matter of urgency. It will significantly contribute to the growth of information technology in the field of financial accounting.